Farmers' participatory selection of new rice varieties to boost production under temperate agro-ecosystems - S Najeeb; F A Sheikh; G A Parray; A B Shikari; G zaffar; S C Kashyp; M A Ganie; A B Shah (Journal of Integrative Agriculture, 2018)
In mountain agriculture, early maturity, high grain yield and high biomass are generally considered as farmer preferred traits in rice crop in addition to a multiple set of traits collectively responsible for variety adoption or rejection. The varieties tested only on station evaluation trials without taking the data from the farmers' fields by not including farmers as partners for variety evaluation are the reasons of low adoption of varieties. In this regard, a participatory methodology was followed by conducting a number of participatory trials in the farmers' fields during 2012–2014 in six districts of Kashmir Valley, India. The mother trials in the farmers' fields showed that the test variety SKUA-408 consistently and significantly out yielded Jhelum and farmers' variety followed by Shalimar rice 3 (SR3). The other released varieties like SR1 and SR2 could not perform nicely in the farmers' fields because of late maturity. After making the t-test comparison of baby trials (paired plots), the mean yield superiority of test varieties SKUA-408, SR3, and SKUA-403 over farmers' variety during 2013 was around 23, 25, and 22%, respectively, whereas in 2014 the respective yield advantage was recorded as 16.3, 17.7, and 16.2%. In all districts, SKUA-408 and SR3 were significantly preferred by farmers (P<0.05 or 0.01) in terms of pre-harvest traits namely, tillering ability and general phenotypic acceptability, early maturity and biomass and for post-harvest traits such as general cooking quality besides, the intention to grow the variety for next year. Adoption and dissemination of SKUA-408 began in 2014 from the farm-saved seed in the form of farmer to farmer seed exchange. Farmers are the end users of a variety so the decision by the farmers while judging the variety should be taken into consideration to make the varietal choice more effective for its widespread adoption.